(3GdeYLe deG GSJYLe GdeTJed Ydi TjhN GdCFeI GdfHds - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3CeG HYO abO CdM Ydi HYV GdCUMGH ai LeY cJGH GdMSf Xfg ai CUGHI GdUhGH s
(3BNQgG (B:s
(3jfJgi YfO PcQ CMeO Hf eMeO Hf CHj jMji s
(3GfXQ gPG GdeYLe HQbe (B1239 (3JMJ GSe GdeYLe Ydi CSeGA TjhN GdCFeI GdfHds
(3LYdJg Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B285 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs